Análise do processo decisório dos investidores e analistas do mercado financeiro em relação às ações de empresas com patrimônio líquido negativo - Cescon, José Antonio (Universidade do Vale do Rio dos Sinos, 2018)
The process of forming decision-making has in the modern theory of finance the assumption that investors act rationally in the market, are risk-averse, seek to maximize expected utility, that markets are highly efficient, and that investors exploit arbitration opportunities. If this premise is correct, how then explain why investors and financial market analysts acquire, maintain and/or recommend shares of companies with negative equity, since these companies are ready for settlement. This challenge to the unlimited rationality of financial market agents has its basis in behavioral finance. Based on these premises, this thesis sought to understand how the decision-making process of financial market investors and analysts is formed in relation to the purchase/sale/maintenance and/or recommendation of shares of companies with negative equity listed on B3 (Brazil, Stock Exchange and Counter). Firstly, an investment portfolio was set up, whose composition is only of companies that went into negative equity to verify if there were abnormal positive returns for investments in companies in this type of situation. The portfolio was formed by 77 companies out of a total of 208 that had at least one quarter of negative equity in the period of analysis of portfolio returns that was from 1998 to 2016. Comparing the result of this portfolio with risk-free investments (Savings account and CDI) and a similar risk investment (IBrX50), the analysis of the portfolio sought to confirm if it is possible to obtain abnormal positive returns in a given period with investments in companies with negative equity and if this return provided is consistent with the risk ratio / return advocated by the modern theory of finance. The results show that it is possible to obtain abnormal positive results, but they do not meet the risk/return relationship when compared to a risk-free investment. These results served as a basis for the development of the proposed thesis that the formation of the decision-making process by financial market investors and analysts is a partially rational decision process because this process is affected by behavioral aspects. To confirm this thesis, interviews were conducted with investors (22) and financial market analysts (09), who owned, have, recommend, the purchase/sale and/or maintenance of shares of companies with negative equity. The questions of these interviews were supported by the behavioral biases: Mental Accounting; Loss Aversion; Fear to Repentance; Disjunction Effect, Herd Effect, Lottery, Excess of Confidence, Excess of Optimism and Monetary Illusion. The method used was content analysis, based on the assumptions of the Efficient Market Hypothesis (HME) and Behavioral Finance. The results found led to three categories of process in the formation of decision making. The 1st category "Rational Process", meets the HME premise that both the investor and the analysts are rational. The second category "Pseudo-rational Process", partially meets the premise of HME, as it partially meets the premise of behavioral finance. The 3rd category "Behavioral Process" meets the premise of Behavioral Finance. The results demonstrate that individually none of the investors or financial market analysts interviewed can be classified within a specific category, in this sense there is not a totally Rational, Pseudo-rational or Behavioral process.
Keywords: Tomada de decisão; Finanças comportamentais; Vieses comportamentais; Investidores; Analistas do mercado financeiro; Decision making; Behavioral finance; Behavioral bias; Investors; Financial market analysts; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis